Numerical study for atmospheric transport of radioactive materials for hypothetical severe nuclear accident under different meteorological conditions - Ma, Zhenhui; Li, Zhiming; Tang, Xiuhuan; Liu, Longbo; Bao, Lihong; Su, Chunlei; Li, Da; Wang, Baosheng; Zhangsun, Yonggang; Hu, Pan; Ma, Tengyue; Chen, Lixin (Frontiers in Environmental Science, 2024)
A study for atmospheric transport is essential for the consequence assessment of severe nuclear accidents since radionuclides could be released from the nuclear facility into the atmosphere and cause radioactive pollution in the environment. Atmospheric transport behaviors are strongly related with meteorological conditions, which can obviously influence the transport and diffusion characteristics of radioactive materials in the atmosphere; thus, it is meaningful to investigate the coupling effects between meteorological processes and transport behaviors of radioactive materials. To evaluate the influence of meteorological conditions on atmospheric transport, meteorological parameters for different seasons were first acquired by the weather research forecast model. Furthermore, atmospheric transport behaviors of radioactive materials were simulated by the meso-scale numerical model under different meteorological conditions, and numerical analyses were conducted toward transport and deposition behaviors of radioactive materials. In addition, the influence of FDDA (four-dimensional data assimilation) on meteorological parameters and atmospheric transport behaviors was researched. The present study is important for strengthening consequence assessment for severe nuclear accident and made it possible to apply the data assimilation technology in further research works.